Challenges of diversity in intercultural contexts. A quantitative study on black women and men in the management of Pernambuco's Sertão Central (Research, Society and Development, 2022)
The present work aims to analyze the challenges of diversity in intercultural contexts related to the experiences of black women and men in management positions in the Sertão Central of Pernambuco. The study aims to understand the processes of inclusion and exclusion under the focus of gender and race in professional business management activities, whether in the public or private spheres. Thus, evaluating the impacts of structural racism directed at the raciality of black employees, intersecting gender issues, empirically investigating the subjective view of employees related to the process of inclusion and career advancement and describing, in a quantitative way, the others processes and challenges of interculturality and the absence of diversity in the field of public-private management. The findings of the study reveal that the problems of raciality and gender are obstacles and challenges experienced in daily life by black women and men employees and that need to be faced, seeking to consolidate a culture that is more inclusive of diversity.